Evaluasi Implementasi Program Indonesia Pintar (PIP) di SD Negeri 1 Ubung : Analisis Aspek Input dan Process dengan Model CIPP - Dwitya, Ni Desak Made Kartini; Izzati, Rahmatul; Mahirudin, Mahirudin; Nuzile, Nuzile; Candra, Candra (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
The Smart Indonesia Program (PIP) is a strategic policy to expand access to education for underprivileged students. This study aims to evaluate the implementation of PIP at SD Negeri 1 Ubung, West Nusa Tenggara (NTB), focusing on the input and process dimensions of the CIPP evaluation model. The input aspect emphasizes resource readiness and strategies, while the process aspect highlights the dynamics of implementation in the field. The research method used was descriptive qualitative, with data collected through in-depth interviews with the principal and school archive documentation, which were then analyzed descriptively to illustrate the reality of program implementation. The results of the input dimension indicate adequate operational readiness, supported by valid Dapodik DTKS data, a good understanding of regulations, and effective use of communication media for parents at SD Negeri 1 Ubung. However, in the process dimension, technical administrative obstacles occurred that resulted in delays in fund disbursement. The school addressed these obstacles through intensive administrative assistance and preventive supervision by the principal to ensure the funds were used appropriately. This study concludes that although the input aspect met standards, the success of PIP at SD Negeri 1 Ubung depends heavily on the school's ability to manage technical administrative obstacles during the implementation process.